ANTINOCICEPTIVE AND ANTIINFLAMMATORY ACTIVITIES OF STEM BARK OF AN ENDANGERED MEDICINAL PLANT, HILDEGARDIA POPULIFOLIA (ROXB.) SCHOTT AND ENDL. - SARADHA M,; S PAULSAMY, (International Journal of Pharma and Bio Sciences, 2013)
This study examined the antinociceptive and antiinflammatory activities of the stem bark of the traditional medicinal plant, Hildegardia poulifolia (Sterculiaceae), an endangered species. Methanolic bark extract of this species was investigated for the antinociceptive effect by using acetic acid-induced writhing and hot plate methods in albino mice and antiinflammatory activity by carrageenan, formalin and histamine induced paw edema in rats. The dose level at 200mg/kg body weight of test extract of H. populifolia showed significantly better antinociceptive and antiinflammatory activities. The experimental data demonstrated that methanol extract of stem bark of H. populifolia possess remarkable antinociceptive and antiinflammatory activities. Hence, the bark of this species may be a potential bioresource for the manufacturing the drugs of antiinflammatory property.